Sosialisasi Upaya Pencegahan Bullying di SD Negeri 56 Perumnas Poka, Ambon - Ronald Darlly Hukubun; Hektor Dalton Hehanussa; Indra Wati Niapele; Ami Indah Marasabessy; Aprilia Tuasuun; Abdul Norman Kibas; Ivanmorl Ruspanah; Alessandra F. Saija (Lembaga Pengembangan Kinerja Dosen, 2024)
Bullying has become a phenomenon in the world of education, especially education in Indonesia, bullying is not only carried out by adults but also carried out by children in the school environment and society. Nowadays there are many cases of bullying that occur in schools, communities and social media. Efforts to prevent bullying from an early age in schools and in the community can be done by socialization, increasing supervision and providing punishment and sanctions to bullies. Stop bullying can be done in many different ways. One way is to include material about bullying into learning that will have a positive impact on the personal development of students It aims to stop bullying that often occurs in schools. With this, we also conduct socialization counseling on Early Bullying Prevention Efforts. The purpose of this socialization is to educate and shape one's personality so as not to bully in the school environment or community environment.